What factors appear to drive private capital flows to developing countries? : and how does official lending respond? - Dasgupta, Dipak 1994- (Policy research working paper, 2000)
Private portfolio flows to a country tend to rise in response to an increase in the current account deficit, a rise in foreign direct investment flows, higher per capita income, and growth performance. The most important determinant of official lending to a developing country seems to be the external current account balance or a change in international reserves in the country